2018
DOI: 10.2486/indhealth.2017-0190
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and occupational stress—systematic review

Abstract: The aim of this systematic review was to explore studies regarding association between occupational stress and heart rate variability (HRV) during work. We searched PubMed, Web of Science, Scopus, Cinahl and PsycINFO for peer-reviewed articles published in English between January 2005 and September 2017. A total of 10 articles met the inclusion criteria. The included articles were analyzed in terms of study design, study population, assessment of occupational stress and HRV, and the study limitations. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
136
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 63 publications
(227 reference statements)
10
136
2
7
Order By: Relevance
“…Interestingly, chronic work stress measured via the JDC ratio, and acute work stress, were not related to night HRV. These results are partly in line with the findings of two reviews (27,75). Loerbroks et al (75) found significant age-related partial correlations with ERI and HRV, but not JDC in the age group of 35 to 44 years.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Interestingly, chronic work stress measured via the JDC ratio, and acute work stress, were not related to night HRV. These results are partly in line with the findings of two reviews (27,75). Loerbroks et al (75) found significant age-related partial correlations with ERI and HRV, but not JDC in the age group of 35 to 44 years.…”
Section: Discussionsupporting
confidence: 85%
“…Loerbroks et al (75) found significant age-related partial correlations with ERI and HRV, but not JDC in the age group of 35 to 44 years. The review of Järvelin-Pasanen et al (27) contained five studies assessing RMSSD. Of these studies, two studies unanimously reported lower RMSSD levels in stressed individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although short-duration measurements can inform us of the level of mental stress during the time frame or situation of interest, measurements of longer duration provide us with vital information on the recovery of stress. Long-term measurements (24 h or more), as opposed to short-term HRV monitoring, enable assessing stress and recovery patterns Table 6 Overview of HRV parameters, artefact corrections and other information in the included studies during normal working hours as well as during leisure time and during sleep (Jarvelin-Pasanen et al 2018). Only four of the included studies performed long-term measurements and investigated the long-term effects and recovery of mental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Ferner ist die HRV bei Arbeitsnehmer in Schichtarbeit zusätzlich reduziert [22] und lässt sich darüber hinaus zur Einschätzung des Burnout-Risikos und Arbeitsstresses [40] nutzen. Auch in diesen Fällen liegt eine reduzierte HRV vor.…”
Section: Anwendungsgebiete Der Hrv-analyseunclassified